Developing Country Trade Policies and Market Access Issues 1990-2012 - Michalopoulos, Constantine (The World Bank, 2013)
The study presents a comprehensive review of developing country trade policies and market access issues as they evolved over the period 1990-2012. The main findings are, first, that applied tariffs as well as traditional core non-tariff measures have declined significantly over time in both developed and developing countries. Second, the instruments of protection used by developed and developing countries are becoming increasingly similar: trade remedies, especially anti-dumping are the instruments of choice for all except low-income developing countries. Third, agriculture is the main sector where developing countries face access problems in OECD markets. Fourth, regional and other preferential trade agreements are both a result and a cause of the lack of progress in multilateral trade negotiations. They violate the basic World Trade Organization tenet of most favored nation and thus pose a potential threat to the multilateral system and a potential stimulus to further multilateral collaboration. Fifth, sanitary and phytosanitary and technical barriers to trade are being increasingly used by both developed and developing countries but their protective intent is difficult to gauge. There is a need for increased vigilance, transparency, and reporting to ensure that they are not being used as a means of protection of economic interests. Sixth, the service sectors are the most promising area where efforts for further liberalization are needed and may produce significant benefits. And seventh, far less additional protection has been put in place following the 2008 financial crisis compared with what had been feared or what had happened in earlier crises